Constitutional culture - Melero De la Torre, Mariano C. (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: The “constitutional culture” means the “realization” or “actualization” of the Constitution in the practices, habits and attitudes of the public powers and the general citizenship of a political community. This paper tries to explore the forms of interdependence between the constitutional norm and the cultural reality, adding at the end some reflections about the role of judges in a constitutional State.